First Record of Cladonia portentosa (Dufour) Coem. (Cladoniaceae) in Libya and Its Association with Juniperus phoenicea L. (Cupressaceae) at Al-Gabal Al-Akhdar Area - Salem El Shatshat; Aya Balam; Abdalbast Askar; Nagwa Alsagaeir (AlQalam Journal of Medical and Applied Sciences, 2025)
Juniperus phoenicea L. is one of the most important Libyan plants, accounting for approximately 80% of the vegetation cover in the Al-Jabal Al-Akhdar region. This region is characterized by a higher richness and diversity of cryptogams, especially lichens, compared to other Libyan areas. During the last decades, this species has been exposed to invasion by lichens, and for this, we studied the colonization of fruticose lichen that appeared on juniper trees at the Al-Gabal Al-Akhdar area. Three different locations were selected, and the results from the field study showed that the lichen invaded the trees more on the southern-facing slopes when compared with those of the northern-facing slopes. In addition, the second location revealed more invasion compared to the other two study locations. it was clear that the abundance of the invasion was very high and formed a large scale in the area of the study site number two. This lichen is commonly spread on dead plants, especially J. phoenicea and, to a different degree, on other plant species, such as Pistacia lentiscus, Olea europaea, and Rhamnus oleoides. According to the British Society, references, and morphological characteristics, the results showed that the lichen species belongs to the Cladoniaceae family of lichenized fungi in the order Lecanorales, genus Cladonia, species portentosa. This species was recorded for the first time in Libya.